Shighat Akad Nikah Perspektif Ulama Empat Mazhab - Rica Amelia Halim Chan; Khairunnisa Amril (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Ijab is a contract that is conveyed (pronounced) by the wife or guardian either at the beginning or at the end. Meanwhile, kabul is a statement of approval for the ijab that has been determined. The pronunciation used in the marriage contract should be able to show the intention of marriage, both in terms of material and substance. In this case, there is a difference of opinion among scholars. For this reason, according to the author, it is necessary to conduct a study on this. The method used by the author is normative juridical. Imam Hanafi and Imam Maliki argue that all redactions that indicate the intention of marriage can be used, then Imam Maliki adds a condition, namely accompanied by the mention of dowry. Meanwhile, according to Imam Shafi'i and Imam Hambali, the validity of marriage is only by the word nikah or marriage and derivatives of these two words.